2019
DOI: 10.1097/mpg.0000000000002177
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Acute Pancreatitis in Taiwan

Abstract: Objective:Pediatric acute pancreatitis (AP) may be different from adult AP in various respects. This study focuses on the epidemiology and medical resource use of pediatric AP in Taiwan.Methods:Patients aged 0 to 18 years with AP were identified from the Taiwan National Health Insurance Research Database based on the International Classification of Diseases, Ninth Revision code of AP 577.0. The medical resource use was measured by length of hospital stay and hospital charges.Results:Between 2000 and 2013, a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Although incidence of all 10 overlapping studies were reported alongside all other studies in the tables, only 4 were included in the meta-analyses and figures. 3,[30][31][32] In total, 44 studies, from the following regions, met our inclusion criteria: Europe (n ¼ 24 10,12,13, ), North America (n ¼ 11 3,4,9,[27][28][29][30][31][53][54][55] ), South America (n ¼ 1 56 ), Asia (n ¼ 5 [57][58][59][60][61] ), and Oceania (n ¼ 3 [62][63][64] ). The 4 studies reporting the incidence of acute pancreatitis in children exclusively were North America (n ¼ 2 54,55 ), Asia (n ¼ 1 57 ), and Oceania (n ¼ 1 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although incidence of all 10 overlapping studies were reported alongside all other studies in the tables, only 4 were included in the meta-analyses and figures. 3,[30][31][32] In total, 44 studies, from the following regions, met our inclusion criteria: Europe (n ¼ 24 10,12,13, ), North America (n ¼ 11 3,4,9,[27][28][29][30][31][53][54][55] ), South America (n ¼ 1 56 ), Asia (n ¼ 5 [57][58][59][60][61] ), and Oceania (n ¼ 3 [62][63][64] ). The 4 studies reporting the incidence of acute pancreatitis in children exclusively were North America (n ¼ 2 54,55 ), Asia (n ¼ 1 57 ), and Oceania (n ¼ 1 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…3,[30][31][32] In total, 44 studies, from the following regions, met our inclusion criteria: Europe (n ¼ 24 10,12,13, ), North America (n ¼ 11 3,4,9,[27][28][29][30][31][53][54][55] ), South America (n ¼ 1 56 ), Asia (n ¼ 5 [57][58][59][60][61] ), and Oceania (n ¼ 3 [62][63][64] ). The 4 studies reporting the incidence of acute pancreatitis in children exclusively were North America (n ¼ 2 54,55 ), Asia (n ¼ 1 57 ), and Oceania (n ¼ 1 63 ). Details of each study are provided in an article descriptors table (Supplementary Table 3): country and region, population representativeness, study period, first presentation or first and recurrent presentations of acute pancreatitis, context of pancreatitis data gathered (eg, admission, discharge, or emergency), diagnosis method (ie, ICD codes and chart review), and etiology of acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Pancreatitis has been reported in all pediatric age groups with no significant sex differences in any of the age groups. 1,3,4 The INSPPIRE (INternational Study Group of Pediatric Pancreatitis: In Search for a CuRE) Group has categorized AP, acute recurrent pancreatitis (ARP), and chronic pancreatitis (CP) based on the natural history of the disease. 6,7 Studies have reported that 12.2-34.5% of children with AP have recurrence of the disease.…”
Section: Introductionmentioning
confidence: 92%
“…Pediatric AP has increased in incidence to the current estimate of 3.6-13.2/100 000 1 in the last two decades. [2][3][4] Its etiology is quite different from that of adults. 5 Gallstones, medications, idiopathic and systemic illness are the most common causes of pediatric AP.…”
Section: Introductionmentioning
confidence: 99%